The Pursuance And Implementation Of Informed Consent Law Towards Vaccination Service Based On 1464/Menkes/Per/X/2010 About Permission And Implementation Of Midwife Practice In Self-Proclaimed Midwives In Semarang - Fitriani Nur Damayanti; Siti Nurjanah; Dewi Puspitaningrum (Universitas Muhammadiyah Semarang, 2016)
Abstract. In providing vaccination services can be done by health workers to give medical consent (informed consent).Informed consent is a term often used for the translation of the approval of medical action. Informed Consent in the medical world we are actually still relatively new. The use of informed consent to health care is still so low, and 30% had experienced midwives maternal perinatal audit due to the demands of patients who do not agree on its medical action and the absence of proof of informed consent in medical record. Purpose : To describe Compliance Midwives in Informed Consent Law Enforcement Against Vaccination Services Based Permenkes 1464 / Menkes / Per / X / 2010 on the Permissions and Implementation of Self-proclaimed Midwives in Semarang. Methods: Descriptive study the necessary data in the form of primary data and secondary data. The sample in this study is Self-proclaimed Midwife in Semarang 30 midwives. Sampling was done by way of non probality sampling technique is purposive sampling. Results: BPM obedient to fill informed consent as much as 40% and BPM are not obedient to fill informed consent as much as 60%.BPM which have informed consent vaccination by 33% and BPM do not have informed consent vaccination as much as 67%. The application of informed consent when the initial vaccination visit as much as 70% and the application of informed consent every time vaccination visit as much as 30%. Conclusion: Most BPM disobedient to fill informed consent, most BPM does not have the informed consent of vaccination and the majority of the application of informed consent at the time of initial BPM vaccination visit.